High-security image encryption by multiplexing phase encoding in domains of dual optical transforms - Li, Zhihui; Gao, Bin; Pan, Xiaoou; Li, Linlin; Wang, Chenxuan; Zuo, Weizhuo; Ji, Yu; Liu, Shutian; Liu, Zhengjun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
A novel optical image encryption is proposed based on multiplexing of the random phase encoding with shift and rotation operations in domains of two transforms, extended fractional Fourier transform (eFrFT) and Fresnel transform. The original image is subjected to eFrFT with the action of the random phase mask. The mask is shifted and rotated to enhance the security of this encryption method. The image obtained from eFrFT is entered into Fresnel diffraction by the use of the phase mask to obtain the final encrypted image. We plan for the phase keys to be multiplexed in order to decrease the amount of keys that need to be stored in an application. Here, the displacement, rotation angle, and wavelength in this system can be used as additional keys to improve the security and reliability of the encryption system. Numerical experiments are conducted to verify the effectiveness and security of the method. The findings demonstrate that the keys are sufficiently sensitive for high security.
Optica Applicata, Vol. 53, 2023, nr 3, s. 447-466
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; extended fractional Fourier transform; geometric operations; random phase encoding